Teknik copywriting pada media sosial perpustakaan di Pontianak sebagai strategi pemasaran digital - Hanum, Atiqa Nur Latifa; Priyadi, Antonius Totok (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This paper aims to identify copywriting techniques used in managing Instagram media of various libraries in Pontianak and the extent of their impact on the target users’ decision to use the library as a learning resource. Data Collection Methods. We used a qualitative approach with virtual observation, literature studies, semi-structured interviews with eight users as participants. Data Analysis. We used data reduction, data presentation to draw conclusion. We used triangulation, cross-checking on key informants and specialists to validate the results. Results and Discussion. Copywriting techniques have not been carried out by all library managers so that the AIDA formula is not visible in every instagram content. Inconsistency in the application of copywriting formula affects the interest of library users in seeing to the information delivered through instagram content. The inconsistency was influenced by librarian’s knowledge and copywriting skills. The library received a positive response marked by library visits, collection utilization, and user participation which increased (although not significantly) because marketing strategies need to be improved. Conclusion. Library managers still focus on quantity and pay less attention to the quality of instagram content so that improving copywriting skills is less of a concern.